Analysis of Legal Gap in Protecting The Rights of Persons With Disabilities in Timor-Leste - Cruz, Carolina da; Soares, Delfin (J-CEKI : Jurnal Cendekia Ilmiah, 2026)
The purpose of this study is to determine and explain the analysis of legal gaps in the protection of the rights of persons with disabilities in Timor-Leste and to determine and explain the factors that influence legal gaps in the protection of the rights of persons with disabilities in Timor-Leste. This research approach uses a normative juridical approach. The research used to complete this study is descriptive analysis. Data collection techniques were conducted through literature and document studies. All collected data, both primary and secondary, will be analyzed qualitatively using a normative legal approach. The data will then be presented descriptively and concluded. Based on the results of the conclusion that the analysis of legal gaps in the protection of the rights of persons with disabilities in Timor-Leste shows a gap between existing laws and regulations and their implementation in the field, as well as differences in the emphasis of national law with international instruments such as the Convention on the Rights of Persons with Disabilities (CRPD) which has been ratified by Timor-Leste. This gap appears in the form of a lack of comprehensive specific laws for disabilities, limited resources and infrastructure, and a lack of public and government awareness regarding the rights of persons with disabilities. Factors contributing to the gap in the protection of the rights of persons with disabilities in Timor-Leste include the lack of ratification of the UN Convention on the Rights of Persons with Disabilities (UNCRPD), socio-cultural stigma and discrimination, poverty that exacerbates disabilities, and barriers to access to education, employment, and other social services. A lack of commitment and effective policy implementation mechanisms at the government and community levels also contribute to this gap